IMPLEMENTASI HUKUM RAHASIA DAGANG SEBAGAI HAK KEKAYAAN INTELEKTUAL DI ERA DIGITAL - Ulya, Widadatul (JIPRO: Journal of Intellectual Property, 2023)
Business actors use digital media in various forms to support market expansion. Various information related to production methods and marketing methods through digital media is no longer in line with the legal concept of trade secret protection in Indonesia. It seems that business actors have no worries about a decrease in economic value when the production methods used are disseminated using social media. This study aims to analyze the implementation of trade secret law as intellectual property rights in the digital era. This normative research uses qualitative methods and a phenomenological approach. Data was collected through literature study, observation, and interviews. The results of the study show that the implementation of trade secret legal protection is private or individualistic. If a business actor disseminates trade secret information, the information will no longer be the object of a trade secret and will not receive legal protection as stipulated in Law No.30/2000.